Mobile apps application to improve safety and health knowledge, attitude and practice among university students. - Sharifah Norkhadijah, Syed Ismail; Josfirin Uding, Rangga; Irniza, Rasdi; Umi Raihana, Abd Rahman; Abu Samah, Mohd Armi (Universiti Putra Malaysia, 2018)
The application of M-learning or mobile application (app) as a tool to disseminate occupational safety and health (OSH) information among students and staff in the university, to replace the use of conventional noticeboard was assessed in this study. Materials and Methods: Study was conducted between February to March 2016 and involved 124 respondents from health sciences program in Universiti Putra Malaysia. OSH information was incorporated into a mobile-app using online software and respondents were requested to use the app for fourteen days. A self-administered questionnaire was used to assess the level of knowledge, attitude and practice of respondents before and after using the app. Results: The mobile app has significantly increased the knowledge score among respondents (z = -7.331, p<0.001). The mean (SD) of knowledge score has increased from 24.39 (5.84) to 30.40 (4.97). The attitude score also has significantly increased from 12.85 (2.04) to 14.02 (2.42) (z= -4.587, p<0.001). The mobile app was not significantly changed the practice (z= -0.688, p=0.491) and the perception among respondents (z= -0.337, p=0.736). Respondents stated that the app was user-friendly (49.4%, N=61), easy to access (N= 64, 51.6%), and have interesting contents (N= 63, 50.8%). They believed continuous used of the app may improve their knowledge (N= 64, 51.6%), and increase their awareness (N= 67, 54.0%) on safety and health. Conclusion: The M-learning (mobile app) has a potential to be used to promote the safety and health culture among students on the campus.